Transformative agency and desistance from crime. (July 2013) - King, Sam
This article provides a discussion of human agency, conceptualized as a transformative aspect of desistance from crime. It is argued here that existing conceptualizations of agency are vague or underexplored, and that a framework based upon the work of Emirbayer and Mische (1998) offers a more comprehensive overview of the manner in which individuals approach desistance. This follows other recent work (for example, Paternoster and Bushway, 2009), in arguing that desistance involves the envisioning of an alternative future identity, and that this is one aspect of agency in the desistance process. However, it is argued here that the deployment of such agency is conditioned by social context and that this delimits the range of future possibilities available. This is illustrated with two cases as examples from recent research in this area.